GOOD CORPORATE GOVERNANCE DAN KINERJA PERBANKAN SYARIAH - Riziqiyah, Metiya Fatikhatur; Prayogi, Agung (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
Performance is one of the things that can cause agency problems in the company. This is because performance is only made by some people in the company. For this reason, it is necessary to have good corporate governance to improve the supervisory mechanism within the company. The purpose of this study is to analyze the effect of the board of commissioners, audit committee and sharia supervisory board on the performance of Islamic banking. The research population is all Islamic banking registered with OJK for the period 2017-2021. The research sample was obtained by purposive sampling technique so as to produce as many as 9 Islamic banking. The research data were analyzed using multiple regression linear regression. The results show that the board of commissioners has no effect on the performance of Islamic banking. The audit committee is able to improve the performance of Islamic banking. The sharia supervisory board has a negative effect on the performance of Islamic banking. Based on the results of the study, it is necessary to increase the ability and competence of the sharia supervisory board in sharia banking to provide positive performance, strengthen the audit committee in sharia banking and maximize the role of the board of commissioners in the company.